2015
DOI: 10.1007/s11837-015-1626-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Biomaterials on Cancer Stem Cell Enrichment and Behavior

Abstract: The theory of cancer stem cells (CSCs) and their role in cancer metastasis, tumorigenicity and resistance to therapy is slowly shifting the emphasis on the search for cancer cure: more evidence is surfacing that a successful therapy should be geared against this rare cancer cell population. Unfortunately, CSCs are difficult to culture in vitro which severely limits the progress of CSC research. This review gives a brief overview of CSCs and their microenvironment, with particular focus on studies that used in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…There are few specialized instruments to artificially generate mechanical force, like the commerciallyavailable FlexCell FX-5000 compression system [99]. Scientists have invested in biomaterials and parameters like differential drug-sensitivity to enrich and perpetually culture CSCs in vitro [100].…”
Section: Tools For Novel Therapeutic Discoverymentioning
confidence: 99%
“…There are few specialized instruments to artificially generate mechanical force, like the commerciallyavailable FlexCell FX-5000 compression system [99]. Scientists have invested in biomaterials and parameters like differential drug-sensitivity to enrich and perpetually culture CSCs in vitro [100].…”
Section: Tools For Novel Therapeutic Discoverymentioning
confidence: 99%
“…Generally, cells conventionally require attachment to the surfaces of cell culture vessels in the presence of a culture medium. However, the attachment is not always necessary for the survival and proliferation of CSCs forming spheres [48,49]. Accordingly, inert biological materials lacking cell attachment could provide a 3D environment.…”
Section: Requirement Of Biomaterials In Csc Culturementioning
confidence: 99%
“…detin enamel, cementum, and pulp. Ordikhani, Yonghyun, & Zustiak [7] showed the dependency of bio-medical properties and growth of cancer stem cells. Also, they found that the characteristics of the cancer stem cells can be affected by the interfaces involved during the growth of biomaterials.…”
Section: Aplications Of Interfacial Science and Rheologymentioning
confidence: 99%